An update on ox-LDL-inducing vascular smooth muscle cell-derived foam cells in atherosclerosis - Guo, Jingjing; Du, Laijing (Frontiers in Cell and Developmental Biology, 2024)
Excess cholesterol accumulation induces accumulation of foam cells, eventually accelerating atherosclerosis progress. Historically, the mechanisms of macrophage-derived foam cells attracted extensive attention because of their central role in plaque development, which was challenged by lineage tracing in union with single-cell sequencing (sc-seq). Accumulated studies uncover how vascular smooth muscle cells (VSMCs) proliferate and migrate to the vascular intima and accumulate, then transform into foam cells induced by surplus lipid, at last, accounting for 30% to 70%, which become the main component of foam cells in atherosclerotic plaques of both mice and humans. Therefore, the mechanisms of VSMC-derived foam cells have been captured more attention. The review intends to summarize the mechanism of transformation of VSMCs into foam cells induced by oxidized low-density lipoproteins (ox-LDL) in atherosclerosis.